Alternatives To Punishment For Deprivation Of Liberty In Juvenile Cases - mikail, Tamim; Alsharaani, Fadi (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study dealt with the penalty of deprivation of liberty in the achievement of its punitive purposes in accordance with the vision of contemporary criminal policy and its negative effects and high expenses<Accordingly the state has endeavored in the framework of the development of its penal systems to limit its use and to seek alternative solutions which were replaced by alternatives to freedom related sanctions as a modern means of reform to counter the criminal phenomenon at least costs and a modern punitive concept. Our research dealt with the sentence of the alternative punishment for imprisonment or imprisonment when it comes to children who violate the law as the foundation of society and the nucleus of the future, it is a new approach available to the criminal judge to choose what suits the case of the event and the victims interest and the context and social and legal satisfaction, the signing of the appropriate alternative punishment to the juvenile concludes the legal system of the disavantages of the deprivation of liberty and provides him with punitive treatment outside the walls of the prison or the reform school which will facilitate his rehabilitation and reintegration within the social, fabric and contributes to the achievement of security and justice in the concept of modern penal policy. تناولت الدراسة قصور العقوبة السالبة للحرية في تحقيق اغراضها العقابية وفق رؤية السياسة الجزائية المعاصرة وأثارها السلبية وارتفاع نفقاتها, وبناء على ذلك سعت الدول في اطار تطوير أنظمتها العقابية إلى الحد من استخدامها والبحث عن حلول بديلة اطلقوا عليها بدائل العقوبات السالبة للحرية كوسيلة اصلاحية حديثة لمواجهة الظاهرة الإجرامية باقل التكاليف وبمفهوم عقابي عصري . وبحثنا هذا تطرق للحكم بالعقوبة البديلة عن الحبس أو السجن عندما يتعلق الأمر بالأطفال المخالفين للقانون كونهم عماد المجتمع ونواة المستقبل, وقد خصهم المشرع بأحكام متفردة نظراً لخصوصيتهم العمرية, واعتباره منهج جديد يتاح امام القاضي الجزائي لاختيار ما هو ملاءم لحالة الحدث ومصلحة الضحية وللسياق والرضا الاجتماعي والقانوني , فتوقيع العقوبة البديلة المناسبة على الحدث يخلص المنظومة القانونية من مساوئ العقوبات السالبة للحرية ويوفر له معاملة عقابية خارج اسوار (السجن) او المدرسة الاصلاحية والتي من شأنها تسهيل تأهيله واعادة ادماجه داخل النسيج الاجتماعي, وتساهم في تحقيق الأمن والعدالة في مفهوم السياسة الجزئية الحديثة.